Message appeal and presentation order of public service advertisement: an experimental study of egg enriched with omega-3 promotion - Suci Paramitasari Syahlani; Bernardinus Maria Purwanto; Mujtahidah Anggrian Ummul Muzayyanah (Universitas Hayam Wuruk Perbanas, 2014)
Some manufacturers have strengthened promotion by including the third party reviews on leaflet in the product packaging to gain a better market response. Third Party Organization (TPO) endorsers in rational appeal advertisement did not perform well compared to those in emotional appeal advertisement. This study analyzes the effect of emotional and rational appeal advertisements on perceived persuasion and presentation order identity of third party organization endorser and message content in advertising on perceived persuasion. Experimental laboratory with factorialdesign 2×2 advertisements type (rational vs. emotional) and presentation order of identification source and message (recency vs. primacy) were done on graduate students in Faculty of Animal Science, Gadjah Mada University, using random assignment to put subjects to reduce bias. It shows that rational and emotional appeals has no significant effect on perceived persuasion where the perceived persuasion average of rational advertisements effect was 5.6453 compared to 5.6247 on emotional advertisements effect. Furthermore, in rational appeal advertisement therecency presentation order affect higher perceived persuasion (p<0.01) that it was 6.0000 than primacy presentation order which was 5.2907. However, in emotional type public service, presentation order has no effect to the perceived persuasion which was 5.5275 in recency presentation order compare to 5.6822 in primacy presentation order.